Respuesta :
Are you sure this question is complete?
(7a - a²)
- (-4 + 3a²)
==========
(7a - a²)
+ (4 - 3a²)
==========
7a + 4 - 4a² = - 4a² + 7a + 4 ...//
(7a - a²)
- (-4 + 3a²)
==========
(7a - a²)
+ (4 - 3a²)
==========
7a + 4 - 4a² = - 4a² + 7a + 4 ...//
ANSWER
[tex]4 + 7a - 4{a}^{2}[/tex]
EXPLANATION
We want to take,
[tex] - 4 + 3 {a}^{2} [/tex]
from
[tex]7a - {a}^{2} [/tex]
Mathematically we can write this statement as,
[tex](7 a - {a}^{2} ) - ( - 4 + 3 {a}^{2} )[/tex]
We use the distributive property to expand to obtain,
[tex]7 a - {a}^{2} + 4 - 3 {a}^{2} [/tex]
We regroup to obtain,
[tex]4 + 7a - {a}^{2} - 3 {a}^{2} [/tex]
This simplifies to
[tex]4 + 7a - 4{a}^{2} [/tex]
[tex]4 + 7a - 4{a}^{2}[/tex]
EXPLANATION
We want to take,
[tex] - 4 + 3 {a}^{2} [/tex]
from
[tex]7a - {a}^{2} [/tex]
Mathematically we can write this statement as,
[tex](7 a - {a}^{2} ) - ( - 4 + 3 {a}^{2} )[/tex]
We use the distributive property to expand to obtain,
[tex]7 a - {a}^{2} + 4 - 3 {a}^{2} [/tex]
We regroup to obtain,
[tex]4 + 7a - {a}^{2} - 3 {a}^{2} [/tex]
This simplifies to
[tex]4 + 7a - 4{a}^{2} [/tex]